IN-VITRO INHIBITION OF SPORES GERMINATION OF ALTERNARIA-SOLANI BY 3 FUNGICIDES - Konno, Y. T.; Machado, J. O.; Churatamasca, MGC (Soc Brasileira Microbiologia, 1994)
In vitro inhibition of the of spores germination of Alternaria solani by iprodione, chlorothalonil, and anilazine at different dosages was studied. The highest concentration of active ingredient studied for each fungicide was equivalent to that recommended for the control of the early blight, under field conditions: 0.75; 1.80 and 1.44 g, respectively, of iprodione, chlorothalonil and anilazine per litre of water. A series of two-fold diluitions of each original concentration was studied in additional nine experiments. Eah of the three fungicides showed total in vitro spore inhibition at the highest rate, at six hours of incubation. At nine hours, only analazine mantained its full inhibition activity. The inhibition activity of iprodione decreased suddenly after 1/2 dilution, so that at the 1/8 dilution a total loss of inhibitory activity was observed. Chlorothalonil showed a progressive and slighter decrease of its activity as the dilution rate increased.Analizine showed a high inhibitory activity at higher dilutions, without any loss up to 1/128 dilution. Even at 1/512 dilution, its activity was so high that only 20% of spore germination was observed at six or nine hours of incubation.
Keywords: ALTERNARIA SOLANI; SPORE GERMINATION; FUNGICIDES; IN-VITRO INHIBITION